1980
DOI: 10.1093/rheumatology/19.4.252
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Efficiency of Three Types of Crutches Using Oxygen Consumption

Abstract: Because the axillary crutch can cause axillary artery thrombosis and crutch palsy, the elbow crutch is more frequently used. Canadian crutches combine features of both the axilla and elbow crutches. A previous study examined any advantages in terms of energy cost using heart rate. The present study re-evaluates the energy cost by using the measurement of oxygen consumption. The study further suggests that the Canadian crutches have advantages in terms of energy cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…T h e present data support numerous previously rep r t e d findings that the energy cost of assisted ambulation is greater than the energy cost of UA (1,4,5,(8)(9)(10)(11).…”
Section: Dlscusslonsupporting
confidence: 89%
See 1 more Smart Citation
“…T h e present data support numerous previously rep r t e d findings that the energy cost of assisted ambulation is greater than the energy cost of UA (1,4,5,(8)(9)(10)(11).…”
Section: Dlscusslonsupporting
confidence: 89%
“…Although many studies have compared the oxygen consumption of ambulation with different crutch types (1,4,5,6,7,8,11,15), few studies have examined walker ambulation (2.3). Cordrey et al (3), in 1958, compared the oxygen cost of ambulation using crutches and a walker.…”
mentioning
confidence: 99%
“…One study assessed healthy individuals who were trained to use crutches and patients with sports injuries who had been using crutches for at least six weeks; the increase in energy expenditure was twofold to threefold greater than when walking without crutches [12]. Another study on the use of crutches in healthy young individuals also demonstrated an increase in energy expenditure when walking with crutches in comparison to walking without crutches, along with a reduction in the distance traveled and an increase in perceived exertion among these individuals [13]. A twofold increase in energy expenditure during gait with crutches when compared to gait without crutches was also described in another study on healthy individuals [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, both crutches and walkers require greater energy expenditure than normal gait. Studies on healthy individuals using a cane have also demonstrated an increase in energy expenditure when compared to normal gait [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Proper crutch use, by supporting loads through the arms, increases the energy expenditure of walking [1,[3][4][5][6][7]. The high energy cost may lead some users to support weight through the axillary support, which some evidence suggests is easier, and may also keep others from ambulating upright altogether.…”
Section: Introductionmentioning
confidence: 99%